Menstrual Patterns of Reproductive Age Group Women and Their Association with Thyroid Dysfunctions (Medical Forum Monthly, 2023)
Objective: This study was designed to evaluate the menstrual cycle patterns including cycle-specific characteristics and explore their relationship with thyroid hormones by measuring the levels of urine hormones in premenopausal women.Study Design: Prospective Cohort StudyPlace and Duration of Study: This study was conducted at the District Head Quarter Hospital Swabi from August 2021 to August 2022.Materials and Methods: This prospective cohort study was conducted to evaluate the menstrual patterns and thyroid association among reproductive women. Data was collected by a pre-designed questionnaire and clinical diagnosis of thyroid performed by physicians. Menses were defined as two consecutive days of bleeding proceeding by three consecutive days of spoting. For monitoring, menstrual cycle patients were asked to submit their first urine void sample and kept their daily menstrual diaries for at least three menstrual cycles. We used univariate analysis for the distribution of each hormone. The log method was used to transform the TSH into a normal distribution. A linear mixed random effect model was used for those results reporting single outcomes.Results: This study recruited 140 women with irregular menstrual patterns. Out of 140, a total of 52 cases of oligomenorrhea, 12 cases of neuropathic, 43 cases of polymenorrhagia, and 33 cases of menorrhagia were detected. These women reported a total of 423 cycles. We recruited cases between the age range of 18 to 45 years. A high association was observed between total T4 and Pd3G and E13G throughout the follicular and luteal phases. At various timeframes, we observed a high association of total and free T3 with high E13G concentrations. These T3 levels were also associated with Pd3G.Conclusion: We observed that thyroid hormone levels were associated with several menstrual cycles. Across the menstrual cycle, a positive correlation between T4 and T3 indicates the effect of hormones on the female reproductive system.